PELAKSANAAN PROGRAM LINGKUNGAN INDUSTRI KECIL INDUSTRI HASIL TEMBAKAU (LIK-IHT) MELALUI PEMANFAATAN DANA BAGI HASIL CUKAI HASIL TEMBAKAU DI KABUPATEN KUDUS TAHUN 2009-2015 - anggraeni, ria; harsasto, priyatno; manar, dzunuwanus ghulam (Journal of Politic and Government Studies, 2016)
This study to find out the implementation of the small industrial area-tobacco product industry (LIK-IHT) for the period of 2009-2015 and the problems and crucial issues facing the implementation of the small industrial area-tobacco product industry (LIK-IHT).The study applied a descriptive-qualitative method using primary and secondary data. The primary data consisted of documents, archives, and human behaviors, either verbal or nonverbal. Study informants were dedtermined by a purposive sampling. Techniques of data collection used in this study consisted of interview, observation and documentation.The small industrial area-tobacco product industry (LIK-IHT) is one of leading programs of Kudus Regency, which had a purpose of providing facilities to small entrepreneurs in tobacco industry in order to survive due to the promulgation of the Minister of Financial Affairs Decree No. 200/PMK.04/2008 on Methods of Provision, Defunction, and Removal of Nomor Pokok Pengusaha Barang Kena Cukai for Tobacco Factories and Importers, which requires that cigarette firms have to possess and to make use of at least 200 meter-square area.The program began in 2009 from the allocation of the Tobacco Excise Revenue Sharing Fund (DBHCHT) of Kudus Regency. The facilities provided in the LIK-IHT consisted 11 production buidings, a laboratory, a cigarette association building, wastewater processing installation (IPAL), mushola, shops, and other supporting facilities. However, problems arose during the making of the LIK-IHT due to ineffectiveness of the facilities and infrastructures as well as budget inefficiency.This study extends the literature as it may be alternative reference for program evaluation in order to improve performance of the implementation of the LIK-IHT Program in Kudus Regency.Keywords: Program Implementation, LIK-IHT, DBHCHT.